Physiology practical - Ostatníková, Daniela, 1957-; Babinská, Katarína; Važan, Rastislav (Comenius University in Bratislava, 2024)
The guide is designed in a way that is complementary to the lectures and the textbook. The task description allows students to focus on a specific physiological concept and to comprehend it practically. The introduction to the tasks avoids extensive description of theories and details, while giving the basic information about the examined physiological function. On the other hand, we have made careful considerations that the information given in this text is accurate and up-to-date. For each task, the "Report" frame below the "Procedure" part allows for writing down the obtained results and giving answers to additional questions reviewing the students' understanding.The material can help the medical student to organize his/her thinking and understand practical aspect of the studied material in particular areas of physiology. To benefit from the experiments, students should review the respective chapter in the textbook dealing with the topic solved in the experimental settings. ---------- Sprievodca je navrhnutý tak, aby dopĺňal prednášky a učebnicu. Opis úlohy umožňuje žiakom zamerať sa na konkrétny fyziologický pojem a prakticky mu porozumieť. Úvod do úloh sa vyhýba rozsiahlemu opisu teórií a detailov, pričom podáva základné informácie o skúmanej fyziologickej funkcii. Na druhej strane sme starostlivo zvážili, že informácie uvedené v tomto texte sú presné a aktuálne. Pre každú úlohu umožňuje rámček "Správa" pod časťou "Postup" zapísať získané výsledky a dať odpovede na dodatočné otázky, ktoré skúmajú pochopenie študentov. Materiál môže pomôcť študentovi medicíny usporiadať si myslenie a pochopiť praktickú stránku preberanej látky v jednotlivých oblastiach fyziológie. Aby študenti mali z experimentov úžitok, mali by si prečítať príslušnú kapitolu v učebnici, ktorá sa zaoberá témou riešenou v experimentálnom prostredí.